RHEOLOGICAL IMPLICATIONS OF THE THERMAL STRUCTURE OF THE LITHOSPHERE IN THE CONVERGENCE ZONE OF THE EASTERN CARPATHIANS - Andreescu M.; Demetrescu C. (My University, 2001)
Four different thermo-kinematic models for the tectonic evolution of the convergence zone of the Eastern Carpathians are studied, in which processes like the pre-collisional subduction of an oceanic lithosphere, the underthrusting of the European continental margin in collision and the post-collisional thermal relaxation control the long term thermal structure of the study area. The thermal field obtained for each tectonic evolution has been used to evaluate the rheological structure along a NE–SW 500 km long lithospheric cross-section perpendicular to the Eastern Carpathians structures. The thermal structure and rheological behaviour of the lithosphere rocks are discussed in correlation with characteristics of the intermediate-depth seismicity of the active Vrancea region, placed at the southern end of the Eastern Carpathians. In front of the convergence fault and in the East European Platform a mechanical decoupling between crustal and mantle layers of the lithosphere could explain the absence of intermediate-depth earthquakes along the most part of the cross-section. The crust seems to be still coupled with the mantle in a narrow volume of the convergence area in the models including an oceanic subduction process. In this volume the mechanically strong lithosphere (MSL) reaches depths of about 220 km, close to the maximum depth of the seismic activity in the Vrancea region, and the lithosphere effective elastic thickness (EET) has values as high as 80–140 km. The peculiarities of the intermediate-depth seismic activity in the Vrancea area could be interpreted in terms of the rheological behaviour of the crustal and mantle material only if an episode of pre-collisional subduction of an oceanic lithosphere is assumed.